DECISION SUPPORT SYSTEM FOR DETERMINING STUDENT ELIGIBILITY TO PARTICIPATE OF MBKM IN THE INFORMATICS STUDY PROGRAM USING AHP AND TOPSIS - Yan Puspitarani; Fitrah Rumaisa; Sriyani Violina; Feri Sulianta; Ai Rosita (Fakultas Teknik Universitas Lambung Mangkurat, 2023)
To be able to have mastery of various sciences that are useful for experience in the world of work, students are encouraged through the MBKM program. Most students of the Informatics Study Program will choose an internship scheme and independent study in applying for the MBKM. However, the increasing number of students' interest in this program requires the Informatics Study Program to be more selective in analyzing the eligibility of students to take part in the MBKM program it has chosen. For this reason, a decision support system is needed that can assist the study program in determining and assessing the eligibility of these students. This study created a DSS modeling using the Analytical Hierarchy Process (AHP) method and the Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) using 8 criteria.